2018
DOI: 10.3390/en11123269
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Tools to Build Urban-Scale Energy Models: A Review

Abstract: The development of Urban-Scale Energy Modelling (USEM) at the district or city level is currently the goal of many research groups due to the increased interest in evaluating the impact of energy efficiency measures in city environments. Because USEM comprises a great variety of analysis areas, the simulation programs that are able to model urban-scale energy systems actually consist of an assemblage of different particular sub-models. In order to simulate each of the sub-models in USEM, one can choose to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 66 publications
0
44
0
1
Order By: Relevance
“…In this sense, the UWG model is versatile and compatible with building energy simulators such as the EnegyPlus because their databases have an *epw extension. As demonstrated by several authors, this information allows a greater veracity and adjustment of studies on a building´s thermal behavior in an urban environment, as on the effect of the heat island in the construction of building energy consumption profiles Salvati et al, 2019;Sola et al, 2018). The UWG model has a great capacity to sensitively predict the results of the application of different mitigation strategies on the surface temperatures of the elements of the urban-building envelopes (walls, roofs and road).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the UWG model is versatile and compatible with building energy simulators such as the EnegyPlus because their databases have an *epw extension. As demonstrated by several authors, this information allows a greater veracity and adjustment of studies on a building´s thermal behavior in an urban environment, as on the effect of the heat island in the construction of building energy consumption profiles Salvati et al, 2019;Sola et al, 2018). The UWG model has a great capacity to sensitively predict the results of the application of different mitigation strategies on the surface temperatures of the elements of the urban-building envelopes (walls, roofs and road).…”
Section: Discussionmentioning
confidence: 99%
“…Among these models, the Energy Balance Model (EBM) and the Computational Fluid Dynamics -CFD models-were the most reliable and presented satisfactory results. There are 4 types of models for urban climate analysis: mesoscale weather models, microclimate models, energy building models, and human thermal models (Ooka, 2007;Sola & Corchero et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on Urban-Scale Energy Modeling (USEM) have shown the importance of morphological characteristics for the energy consumption of buildings [7]. The influence of urban form is considered important to optimize an energy system, together with the impact of the microclimate in built-up areas [8] and the characteristics of the outdoor environment [9].…”
Section: Research Gapmentioning
confidence: 99%
“…In urban energy design, further improvements of building energy performance and substantial use of green energy can further aid in designing smart homes and low carbon neighorhood cities. Other factors including local microclimate and its relationship to building-energy demand and occupants' behavior modeling should be considered [182]. In addition, authorities should address the privacy issue of releasing measured building energy use so that this information can be used to calibrate urban building-energy models [183].…”
Section: Potential Applications Of Pbamentioning
confidence: 99%